The Adhesion G-Protein-Coupled Receptor, GPR56/ADGRG1, Inhibits Cell–Extracellular Matrix Signaling to Prevent Metastatic Melanoma Growth - Millar, Michelle W.; Corson, Nancy; Xu, Lei (Frontiers in Oncology, 2018)
Metastatic growth is considered a rate limiting step in cancer progression, and upregulation of extracellular matrix (ECM) deposition and cell-ECM signaling are major drivers of this process. Mechanisms to reverse ECM upregulation in cancer could potentially facilitate its prevention and treatment but they are poorly understood. We previously reported that the adhesion G-protein coupled receptor GPR56/ADGRG1 is downregulated in melanoma metastases. Its re-expression inhibited melanoma growth and metastasis and reduced the deposition of fibronectin, a major ECM component. We hypothesize that its effect on fibronectin deposition contributes to its inhibitory role on metastatic growth. To test this, we investigated the function of GPR56 on cell-fibronectin adhesion and its relationship with metastatic growth in melanoma. Our results reveal that GPR56 inhibits melanoma metastatic growth by impeding the expansion of micrometastases to macrometastases. Meanwhile, we present evidence that GPR56 inhibits fibronectin deposition and its downstream signaling, such as phosphorylation of focal adhesion kinase (FAK), during this process. Administration of the FAK inhibitor Y15 perturbed the proliferation of melanoma metastases, supporting a causative link between the cell adhesion defect induced by GPR56 and its inhibition of metastatic growth. Taken together, our results suggest that GPR56 in melanoma metastases inhibits ECM accumulation and adhesion, which contributes to its negative effects on metastatic growth.